Legal aspects of land administration service with land computerization information systems in Sidoarjo (Research, Society and Development, 2020)
The aim of this analysis is referred to several problems which are concerning the Land Administration Service in National Land Agency and Law Aspect of Land Administration Service with the Computerization Information System in BPN Sidoarjo. This research applies the Juridical Normative approach especially in Land Law with the Descriptive and Analytic and qualitative analysis. The result showed that Land Data Management used the information technology which is something that absolutely must be done is related to the characteristics of the land data itself which are multidimensional in nature related to economic, political, defense and security and socio-cultural issues. It can be concluded that information and electronic Transaction, some doubts about the use of electronic land data have found a clarity, especially relating to the electronic documents that are used as a means of proving and electronic data security.